The Theory and Practice of Capital Structure in Developing Countries - Wong, Sau Chan (2014)
This study conducts an analysis of the current capital structure practice amongst the sample companies in developing countries as well as looks into if; and if so how the capital structure practice in developing countries different from that of the developed countries. Since the 1950s there have been many studies pertaining to capital structure theories. The examples are Modigliani and Miller, (1958, 1963); Jenson and Meckling, (1976); Myers, (1984). Most, if not all, the theories on capital structure mentioned relate to the developed countries. This study intends to use the determinants in the theories to analyse the capital structure practice in developing countries. This study also makes a comparison between the capital structures practice in developed countries to that in developing countries. This study analyse 23 developing countries capital structure practice with 11 firm specified determinants. The firm size in developing countries are relatively smaller than developed countries, therefore the firms in developing countries was not able to fully benefit from interest tax saving as per the trade-off theory suggested. In summary, despite the many varying theories on capital structure in developed countries there is no one perfect consensus thus far, potentially due to the different of countries specific factors as well as the changing business environment over time.